2009
DOI: 10.17221/66/2008-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic response to different light intensities and water status of two main Nothofagus species of southern Patagonian forest, Argentina

Abstract: Net photosynthetic rate (A) and stomatal conductance (gs) of leaves of Nothofagus pumilio and N. antarctica seedlings were measured at different photosynthetic photon flux densities (PPFDs, 20, 150, 250, 500, 750, 1,000, 1,500 and 2,200 µmol/m 2 /s) and after 60 minutes of shade to determine the rate of photosynthetic induction after seedling transition from low to high PPFD. A and gs were also measured to evaluate the responses to water stress and the tolerance to waterlogging. N. pumilio had higher A values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 24 publications
3
38
1
10
Order By: Relevance
“…These reductions may be due in part to a decrease in gs, especially if VPD is high, but an additional effect of some degree of damage of the photosynthetic apparatus must be considered for both species to explain photosynthesis reductions. Considering the results from seedlings under suitable water conditions, both species had mean values of net photosynthetic rate similar to those found in other species of the genus (Read and Hill 1985;Martinez Pastur et al 2007;Piper et al 2007;Peri et al 2009) and related genera (e.g. Leuzinger et al 2005;Gallé and Feller 2007).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These reductions may be due in part to a decrease in gs, especially if VPD is high, but an additional effect of some degree of damage of the photosynthetic apparatus must be considered for both species to explain photosynthesis reductions. Considering the results from seedlings under suitable water conditions, both species had mean values of net photosynthetic rate similar to those found in other species of the genus (Read and Hill 1985;Martinez Pastur et al 2007;Piper et al 2007;Peri et al 2009) and related genera (e.g. Leuzinger et al 2005;Gallé and Feller 2007).…”
Section: Discussionsupporting
confidence: 71%
“…For example, the physiological responses of European species of the genus Quercus and Fagus are well known (Cochard et al 2000;Corcuera et al 2002;Lemoine et al 2002;Aranda et al 2004;Lendzion and Leuschner 2008), while the knowledge of the drought response of species in many other regions with Mediterranean-type climate, including northern Patagonia on the western rim of South America, is limited to just a few species (Suarez et al 2004;Gyenge et al 2007;Martinez Pastur et al 2007;Piper et al 2007;Peri et al 2009), or even non-existent for other important forest species.…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to highlight that survival of seedlings and saplings depends on the species' ecophysiological traits. Notofagus antarctica is considered less 'shade tolerant' from a physiological perspective compared to other closely related species such as N. pumilio (Peri et al 2009b). It provides competitive advantages for this tree species to grow in open areas.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Martínez Pastur et al (2011) reported a superior height growth of N. pumilio regeneration beneath the protection of older residual seed trees (45 % crown cover). According to Peri et al (2009) andMartínez Pastur et al (2007), N. pumilio seedlings have higher photosynthetic rates in big gaps or when light availability increases due to silvicultural treatments, and when water is non-limiting. However, when soil moisture becomes a limiting environmental factor (pre-dawn leaf water potential less than -1.7 MPa), the photosynthetic response (and therefore growth) is reduced regardless of light availability.…”
Section: Discussionmentioning
confidence: 99%